Saqqara, Ägypten: Das Grab des Königs Ninetjer - Lacher-Raschdorff, Claudia (e-Forschungsberichte des DAI, 2023)
Saqqara is located on the western bank of the Nile about 25 km south of Cairo. Since 2003 the DAI Cairo has been working on the re-examination of the tomb of Ninetjer, third king of the 2nd Dynasty (ca. 2785 BC). The subterranean system extends over an area of about 77 m × 50 m and is divided into 191 rooms, running through the rock in a maze of winding paths. The work concerning the 2nd Dynasty is nearly finished, while the reuse of the tomb in later periods will be the objective for the following years.